2017
DOI: 10.21048/ijnd.2017.54.1.15441
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Eating Attitudes and Healthy Lifestyle Behaviors of Female Students Studying Nutrition and Dietetics

Abstract: The study seeks to assess eating attitudes and healthy lifestyle behaviors of female students studying Nutrition and Dietetics, a field where dieticians who give right messages about healthy diet are trained. The research was conducted on a total number of 160 female students studying Nutrition and Dietetics. The data were collected through face-to-face interview using questionnaire form. The questionnaire included questions about the socioeconomic features, feeding habits and physical activity levels of stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…HPLP Exercise Scale scores of the students who exercised at least 30 minutes of moderate-intensity intensity 5 times a week were found to be significantly higher than all other groups. Similarly, in the study conducted by Alkan et al with university students, the HPLP Exercise Scale scores of the students with high physical activity level were found to be higher than the other groups (31). In the study of Yalcinkaya et al, The group who exercised 3-4 days or more a week got higher scores in all sub-dimensions of physical activity and overall total (32).…”
Section: Discussionmentioning
confidence: 85%
“…HPLP Exercise Scale scores of the students who exercised at least 30 minutes of moderate-intensity intensity 5 times a week were found to be significantly higher than all other groups. Similarly, in the study conducted by Alkan et al with university students, the HPLP Exercise Scale scores of the students with high physical activity level were found to be higher than the other groups (31). In the study of Yalcinkaya et al, The group who exercised 3-4 days or more a week got higher scores in all sub-dimensions of physical activity and overall total (32).…”
Section: Discussionmentioning
confidence: 85%
“…ere is also a study reporting that there is no significant difference between skipping meals and eating disorders [63]. Another study found that fasting, skipping meals, vomiting, and laxative use were common in adolescents with low body satisfaction and unhealthy weight control behaviors [64].…”
Section: Discussionmentioning
confidence: 99%
“…In the studies conducted with university students, it was observed that students who skip meals tend to have a higher risk of eating disorders [ 60 , 62 ]. There is also a study reporting that there is no significant difference between skipping meals and eating disorders [ 63 ]. Another study found that fasting, skipping meals, vomiting, and laxative use were common in adolescents with low body satisfaction and unhealthy weight control behaviors [ 64 ].…”
Section: Discussionmentioning
confidence: 99%